(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this study, different samples of water are collected from different provinces including, (Babylon , Maysan , Al kut ) which were ( river water ,drainage water and drinking water). Water sampling was during the month of February 2014. The chemical properties of these samples have been determined including ( pH - Ec-Ca-Mg-K - Na - HCO3 and CO3) as well as measured aluminum for each sample and the results were as follows ,it was founded that Ec ranged from( 1 .101 - 5.39) ms / cm ,higher value found in Babylon for drainage water and lower value found in Al kut for drinking water . The values ​​of pH are ranged from( 7.65 -8.26 ) ) and the values ​​for are ranged from (5.26-29.91) meq / L and the values ​​of are ranged from (0.19-1.53) meq / L and values ​​for Cl ranged from (15 - 31) meq / L and the values ​​for CO3 ranged from (0 - 0.1) meq / L and the values ​​for HCO3 ranging from (1.6-7) meq / L and the values ​​for Ca ranging from (3.4-11.8) meq / L and the values ​​for Mg ranging from (4.4-19.4) meq / L and the values ​​for (Al) is very high and ranging from (0.640 to 0.647) ppm, and compared the results with standard specification of Iraq